2017
DOI: 10.1038/bmt.2017.35
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stromal cell infusion to treat steroid-refractory acute GvHD III/IV after hematopoietic stem cell transplantation

Abstract: Acute GvHD (aGvHD) is a life-threatening complication of hematopoietic stem cell transplantation. Frontline therapy for aGvHD consists of corticosteroid administration. However, ∼25% of the patients have a steroid-refractory disease, a sign of poor prognosis. An alternative therapy for steroid-refractory aGvHD is infusion of mesenchymal stromal cells (MSCs). Herein, we report the results of 46 patients treated with MSC infusion as salvage therapy for steroid-refractory aGvHD III/IV (78% grade IV). Patients rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 25 publications
3
56
0
2
Order By: Relevance
“…However, the obtainment of any kind of response (either PR or CR) was sufficient to affect OS. This is consistent with previous studies in patients who, like ours, were refractory to several lines of treatment (Resnick et al, 2013;Kurtzberg et al, 2014;von Dalowski et al, 2016;Muroi et al, 2016;Dotoli et al, 2017;Servais et al, 2018). In contrast, other groups have reported that, when MSCs were administered soon after steroids, only CR are associated with improved OS (Le Blanc et al, 2008;Kebriaei et al, 2009;S anchez-Guijo et al, 2014).…”
supporting
confidence: 94%
“…However, the obtainment of any kind of response (either PR or CR) was sufficient to affect OS. This is consistent with previous studies in patients who, like ours, were refractory to several lines of treatment (Resnick et al, 2013;Kurtzberg et al, 2014;von Dalowski et al, 2016;Muroi et al, 2016;Dotoli et al, 2017;Servais et al, 2018). In contrast, other groups have reported that, when MSCs were administered soon after steroids, only CR are associated with improved OS (Le Blanc et al, 2008;Kebriaei et al, 2009;S anchez-Guijo et al, 2014).…”
supporting
confidence: 94%
“…Bader et al [5] reported a large cohort of patients with refractory aGvHD who received the completely new product “MSC-FFM.” The overall response rate at day +28 as an outcome parameter was 83%. Indeed, these results are very encouraging compared with other aGvHD studies [21, 28, 29, 31, 32]. To our knowledge, so far MSC-FFM offered the best response rates of all MSC preparations in children and especially in adults.…”
Section: Discussion and Perspectivesupporting
confidence: 55%
“…Ball et al [23] demonstrated a better OS (56%) and lower TRM (17%) in patients who received MSCs between days +5 and +12 after steroid initiation compared with treatment between days +13 and +85 (25 and 53%; p = 0.22 and p = 0.06). Dotoli et al [31], Dalowski et al [32], and also Salmenniemi et al [30] reported considerably lower response rates and OS. Bader et al [5] reported a large cohort of patients with refractory aGvHD who received the completely new product “MSC-FFM.” The overall response rate at day +28 as an outcome parameter was 83%.…”
Section: Discussion and Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Dotoli and colleagues published the results of 46 patients treated with MSC infusion as salvage therapy for steroid-refractory acute GvHD III/IV (78% grade IV), recently (41). Patients in this study received a median cumulative dose of 6.81×10 6 MSCs per kg bodyweight in a median of three infusions.…”
Section: Box 2 Effects Of Mscs On Acute Gvhd Symptoms In Different Stmentioning
confidence: 99%